2012
DOI: 10.21930/rcta.vol13_num1_art:236
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de Neohydatothrips signifer Priesner (Thysanoptera: Thripidae) en maracuyá (Passiflora edulis f. flavicarpa Degener) en el departamento del Huila (Colombia)

Abstract: <p>Con un potencial de daño hasta del 95% en terminales vegetativos. El manejo convencional para esta plaga está enfocado hacia el uso de insecticidas químicos restringiendo la exportación de la fruta. En esta investigación se integra un modelo de manejo integrado de plagas (MIP) de trips para el cultivo de maracuyá en tres fincas del municipio de La Plata (Huila). Se establecieron dos parcelas, una, el modelo MIP con liberaciones de <em>Chrysoperla externa </em>(30.000 larvas/ha), aplicación… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
1
2
0
2
Order By: Relevance
“…Having started the applications at the beginning of the flowering stage and making three applications, every 4 weeks, kept the population of thrips low and prevented the number of individuals from increasing significantly, and this effect was maintained by including honey, Inex A in the mixture or without them, observing that in mango cultivation (Figure 8a), this effect is reduced when no adherent is applied. The reduction in the number of thrips at an extract concentration of 10% was similar to that obtained by Monje [57] who reported a mortality of adult thrips similar to chemical treatments, who used Spinosad, Imidacloprid and Thiamethoxan, without the use of adherent, being among the most efficient the extract of A. sativum and onion. Nava-Pérez [58] and Vázquez-Luna [59] indicated that the metabolites present in the extract of A. sativum present repellency, feeding and growth regulation of the larval growth faces of the insect plague.…”
Section: Dynamics Of Adults Of Thrips In the Mango Crop (A) And Of Me...supporting
confidence: 85%
“…Having started the applications at the beginning of the flowering stage and making three applications, every 4 weeks, kept the population of thrips low and prevented the number of individuals from increasing significantly, and this effect was maintained by including honey, Inex A in the mixture or without them, observing that in mango cultivation (Figure 8a), this effect is reduced when no adherent is applied. The reduction in the number of thrips at an extract concentration of 10% was similar to that obtained by Monje [57] who reported a mortality of adult thrips similar to chemical treatments, who used Spinosad, Imidacloprid and Thiamethoxan, without the use of adherent, being among the most efficient the extract of A. sativum and onion. Nava-Pérez [58] and Vázquez-Luna [59] indicated that the metabolites present in the extract of A. sativum present repellency, feeding and growth regulation of the larval growth faces of the insect plague.…”
Section: Dynamics Of Adults Of Thrips In the Mango Crop (A) And Of Me...supporting
confidence: 85%
“…Estos insectos son voladores por lo cual se observa su presencia en el atardecer y la noche (Monje et al, 2012). Loera et al (2001) señala que dentro del ciclo biológico de este insecto se destaca como depredador, el estado larval.…”
Section: Introductionunclassified
“…Con el fin de lograr mayor eficiencia reguladora con C. externa, se debe liberar cuando está en su primer instar larval y cuando los niveles de infestación de la plaga sean de bajos a moderados, como lo afirma Monje (19), quien obtuvo un porcentaje de mortalidad del 76 % de la plaga N. signifer en el cultivo de maracuyá durante todo el estadio larval del depredador C. externa.…”
Section: Chrysoperla Externaunclassified